OpenMP : memory, devices, and tasks : 12th International Workshop on OpenMP, IWOMP 2016, Nara, Japan, October 5-7, 2016, Proceedings /: memory, devices, and tasks : 12th International Workshop on OpenMP, IWOMP 2016, Nara, Japan, October 5-7, 2016, Proceedings. (2016) - Unknown
No abstract available